Representation of Conflict in the Soap Opera “Asmara Gen Z” on SCTV - Putri Vidya Nur Azizah; Farida Nurfalah (Pelopor Publikasi Akademika, 2026)
Generation Z is the first generation to use digital technology and exhibits distinct media consumption characteristics, yet television remains relevant when it presents content, such as soap operas, that resonates with their experiences. This study aims to analyze the representation of conflict in the soap opera “Asmara Gen Z” episode 322 through Robert Entman’s four dimensions of framing to uncover the ideological values and social responsibilities conveyed to Gen Z audiences. The research employs a qualitative approach, utilizing Entman’s framing model analysis and in-depth interviews with six Gen Z informants. The results indicate that the conflict is framed as a personal character conflict reinforced by an inconsistent school policy system. The “9 Ilmu” group is represented as a highly solidary group expected to yield, whereas “Tirta Persada” is depicted as a privileged group making excessive demands. This study concludes that soap operas transmit four paradoxical values: passive adaptive solidarity, empathy, ambiguous distributive justice, and maturity as passivity, collectively reinforcing the ideology of “Privileged Compassion.” Recommendations are directed at soap opera creators to develop narratives that are more attuned to issues of distributive justice, emphasizing solutions centered on personal attitude change rather than systemic reform.